Modeling economic growth in contemporary Czechia - Stavárek, Daniel; Tvrdon, Michal (Emerald Publishing Limited, 2024)
Czechia has been a member state of the European Union for more than eighteen years. During this time, the Czech economy has undertaken a significant transformation. In the past decade alone, the Czech economy has had to cope with several external and internal shocks - the effects of the financial crisis and the subsequent crisis of the real economy, internal recession, and significant economic growth interrupted by the COVID-19 pandemic. Separated into four distinct parts, Modeling Economic Growth in Contemporary Czechia explores economic growth in Czechia from the perspectives of the dynamics of the economy, setting up of the economic policies, functioning of the markets and institutions, and the contribution of specific industry sectors to economic growth. Entrepreneurship and Global Economic Growth is Emerald's cutting edge Global Economic Growth book series, presenting modern examinations of economic growth at national, regional, and global levels. Each book in this series discusses different dimensions of the changing economic and industrial contexts and examines in detail their impact on the nature of growth and development.
Includes index.
Keywords: Economic development -- Czech Republic.; Business & Economics -- Development -- Economic Development.; Economic growth.; Development economics and emerging economies.; elektronické knihy; electronic books